Uncited Publications in MEMS Literature: A Bibliometric Study - Gopalakrishnan, S.; Gopalakrishnan, S.; Bathrinarayanan, A.L.; Tamizhchelvan, M. (DESIDOC Journal of Library & Information Technology, 2015)
In this paper attempt has been made to identify the uncited publications in ‘micro-electro mechanical systems (MEMS) literature which is one of the emerging field in electronics. The search term ‘MEMS’ was used for retrieving literatures from SCOPUS database. A total of 294573 records were identified in the field of MEMS during the period 1970-2013. Out of which, 85146 (28.90 %) records were uncited publications. The uncited paper ranges between 0.09 % and 0.72 %. It can be seen that from 1988 onwards uncitedness has been reduced below the global average and it persists till 2010. Almost 56 % of the uncited publications are from the conference proceedings. 44.56% of China publications in MEMS were uncited followed by India (31.44 %), Japan (24.40 %), and France (19.44 %). Majority of the uncited publications, are of collaborative authors besides the self-citations. Mostly more than four authors’ papers were uncited. Even top author papers were also uncited. The uncitedness may be due to non-awareness of those papers in the MEMS literature. DOI: 10.14429/djlit.35.2.8324